Low-impact strategy for capturing better emergency department injury surveillance data. Issue 6 (18th October 2018) - Brubacher, Jeffrey R; Shih, Yuda; Weng, Jian Ting; Verma, Rahul; Evans, David; Grafstein, Eric
Abstract : Objectives: Injury prevention should be informed by timely surveillance data. Unfortunately, most injury surveillance only captures patients with severe injuries and is not available in real time, hampering prevention efforts. We aimed to develop and pilot a simple injury surveillance strategy that can be integrated into routine emergency department (ED) workflow to collect more robust mechanism of injury information at time of visit for all injured ED patients with minimal impact on workflow. Methods: We reviewed ED injury surveillance systems and considered ED workflow. Forms were developed to collect injury-related information on ED patients and refined to address workload concerns raised by key stakeholders. Research assistants observed ED staff as they registered injured patients and noted the time required to collect data and any ambiguities or concerns encountered. Interobserver agreement was recorded. Results: Injury surveillance questions were based on a modification of the International Classification of External Causes of Injury. Research assistants observed 222 injured patients being admitted by registration clerks. The mean time required to complete the surveillance form was 64.9 s (95% CI 59.9 s to 69.9 s) for paper-based forms (120 cases) and 44.5 s (95% CI 41.7s to 47.4s) with direct electronic data entry (102 cases). Interobserver agreement (26 cases) was 100% for intent (kappa=1.0) of injury and 96% for mechanism of injury (kappa=0.74). Conclusions: We report a simple injury surveillance strategy that ED staff can use to collect meaningful injury data in real time with minimal impact on workflow. This strategy can be adapted to enhance regional injury surveillance efforts.